"The Easier the Better" Preparation of Efficient Photocatalysts—Metastable Poly(heptazine imide) Salts. Issue 32 (20th June 2017) - Chen, Zupeng; Savateev, Aleksandr; Pronkin, Sergey; Papaefthimiou, Vasiliki; Wolff, Christian; Willinger, Marc Georg; Willinger, Elena; Neher, Dieter; Antonietti, Markus; Dontsova, Dariya
Abstract : Cost‐efficient, visible‐light‐driven hydrogen production from water is an attractive potential source of clean, sustainable fuel. Here, it is shown that thermal solid state reactions of traditional carbon nitride precursors (cyanamide, melamine) with NaCl, KCl, or CsCl are a cheap and straightforward way to prepare poly(heptazine imide) alkali metal salts, whose thermodynamic stability decreases upon the increase of the metal atom size. The chemical structure of the prepared salts is confirmed by the results of X‐ray photoelectron and infrared spectroscopies, powder X‐ray diffraction and electron microscopy studies, and, in the case of sodium poly(heptazine imide), additionally by atomic pair distribution function analysis and 2D powder X‐ray diffraction pattern simulations. In contrast, reactions with LiCl yield thermodynamically stable poly(triazine imides). Owing to the metastability and high structural order, the obtained heptazine imide salts are found to be highly active photocatalysts in Rhodamine B and 4‐chlorophenol degradation, and Pt‐assisted sacrificial water reduction reactions under visible light irradiation. The measured hydrogen evolution rates are up to four times higher than those provided by a benchmark photocatalyst, mesoporous graphitic carbon nitride. Moreover, the products are able to photocatalytically reduce water with considerable reaction rates, even when glycerol is used as a sacrificial hole scavenger. Abstract : Mesocrystalline sodium poly(heptazine imide) is directly obtained by the solid‐state reaction of melamine with excess sodium chloride. The product structure is confirmed by in‐depth characterization and simulations. This novel carbon nitride related material is shown to be a highly active photocatalyst for degradation of a model dye and hydrogen evolution using aqueous glycerol solution upon visible‐light irradiation.